THE INFLUENCE OF BRAND IMAGE AND QUALITY OF SERVICE ON CONSUMER BUYING INTEREST IN DELIVERY SERVICES PT PAXEL ALGORITA UNGGUL"PAXEL" - Toha, Ayu Siti H.; Saragih, Desni S.; Emha, Egi Fauzi B.; Fauzi, Moch Lutfi Z.; Ryamizard, Ridwan; Hapsari, Ayuningtyas Y. (CENTRAL ASIA AND THE CAUCASUS, 2022)
The rapid growth of e-commerce business in Indonesia makes freight or package delivery service companies more crowded. The rise of freight forwarding companies makes the competition even tighter, companies are competing to show the advantages and features owned by one of the delivery services called Paxel. Paxel is a newcomer company in the field of freight forwarding services with the advantage of shipping goods with only one day but the majority of people in bandung already know Paxel but rarely use delivery services from Paxel. Therefore, the problem in this study aims to find out how brand image variables and service quality do affect the variables of buying interest in consumers. This research method uses descriptive and verifiative methods with quantitative approaches. The sample used in this study is the people of Bandung Raya and numbered 100 people. This research questionnaire was distributed evenly to the people in the five regions of Bandung Raya using the path of analysis and hypothesis testing. The results of this study can be found that brand image variables and service quality significantly affect consumer buying interest variables to use Paxel freight forwarding services.